3-Dimensional graphene-like structures and applications: general discussion - Backes, Claudia; Behera, Ranjan Kumar; Bellamy-Carter, Abigail; Bianco, Alberto; Caps, Valérie; Casiraghi, Cinzia; Chhowalla, Manish; Criado, Alejandro; Davies, Trevor; Ferrari, Andrea C.; Fornasaro, Stefano; Galembeck, Fernando; et al. (Chemistry of 2-dimensional materials, 2021)
No abstract available